Public expectations towards the roles of the Indonesian house of representatives - Mohammad Hidayaturrahman; Edy Purwanto; Astriana Sinaga; Ahmad Ubaid; Widya Wardhani; Anak Sugiantiningsih (Faculty of Communications Science, Dr. Soetomo University, 2024)
Abstract The People's Representative Council of the Republic of Indonesia (DPR RI) plays an important role in a democratic country, functioning as a means of control for the government in office. With its authority to make laws, set budgets, and supervise government administration, the People's Representative Council of the Republic of Indonesia has a strong position. This research was conducted to understand and analyse the public's perception of the DPR RI in its role. This research uses quantitative descriptive methods. Data was collected using questionnaires from respondents in 26 provinces, consisting of 71 cities and regencies in Indonesia from 2019 to 2022. This study discovered that most Indonesian people see a role for the People's Representative Council of the Republic of Indonesia and that they hope that the DPR will continue to work to create legislation and oversee the government. The existence of the People's Representative Council of the Republic of Indonesia is still of interest to the citizens of the Republic of Indonesia. So far, the ministry has only used mass media as a means of communication and political information. In the future, the parliament needs to use social media, as well as institutional websites, including video conferences and live streaming as a means of political communication in the era of digital democracy. To establish the groundwork, communication will not only be one-way but also two-way between parliament and the public, as well as between the public and parliament.